Experimental Approaches Towards Allergic Asthma Therapy-Murine Asthma Models - Wegmann, Michael; Hauber, Hans P. (Recent Patents on Inflammation & Allergy Drug Discovery, 2010)
Allergic bronchial asthma is a chronic inflammatory disorder of the airways characterized by a T helper 2 (TH2) cell triggered airway eosinophilia, development of airway hyperresponsiveness, mucus hypersecretion and structural changes of the airway wall summarized as airway remodeling. Current asthma therapy aims at controlling the inflammatory response in the airways by using corticosteroids in mild-moderate asthmatics. With increasing disease severity addition of further medication is required and includes long acting β2-agonists or even immune suppressive drugs such as azathioprine, methotrexate or cyclophosphamide. Due to considerable side effects of these drugs especially under high dose treatment conditions controlling moderate-severe asthma represents an unmet medical need. Over the last 15 years mouse models of allergic asthma increased the knowledge about the pathophysiology of allergic asthma dramatically and led to several new therapeutic approaches such as the development of a monoclonal antibody against IgE. However, since TH2 cells seem to play a pivotal role in orchestrating the inflammatory response underlying asthma pathology these cells are predisposed as targets for therapeutic intervention. Thus, the present article further discusses several relevant patents and the current status of experimental approaches towards asthma therapy that aim at neutralizing TH2 cell effector functions, TH2 cell development, TH2 cell recruitment, and immunomodulation.
Keywords: mouse models